Heat Transfer and Ablation Prediction of Carbon/Carbon Composites in a Hypersonic Environment Using Fluid-Thermal-Ablation Multiphysical Coupling - Xuewen Sun; Haibo Yang; Tao Mi (International Journal of Aerospace Engineering)
Carbon/carbon composites are usually used as a thermal protection material in the nose cap and leading edge of hypersonic vehicles. In order to predict the thermal and ablation response of a carbon/carbon model in a hypersonic aerothermal environment, a multiphysical coupling model is established taking into account thermochemical nonequilibrium of a flow field, heat transfer, and ablation of a material. A mesh movement algorithm is implemented to track the ablation recession. The flow field distribution and ablation recession are studied. The results show that the fluid-thermal-ablation coupling model can effectively predict the thermal and ablation response of the material. The temperature and heat flux in the stationary region of the carbon/carbon model change significantly with time. As time goes on, the wall temperature increases and the heat flux decreases. The ablation in the stagnation area is more serious than in the lateral area. The shape of the material changes, and the radius of the leading edge increases after ablation. The fluid-thermal-ablation coupling model can be used to provide reference for the design of a thermal protection system.